2017
DOI: 10.1093/dnares/dsw057
|View full text |Cite
|
Sign up to set email alerts
|

An integrated transcriptomics-guided genome-wide promoter analysis and next-generation proteomics approach to mine factor(s) regulating cellular differentiation

Abstract: Differential next-generation-omics approaches aid in the visualization of biological processes and pave the way for divulging important events and/or interactions leading to a functional output at cellular or systems level. To this end, we undertook an integrated Nextgen transcriptomics and proteomics approach to divulge differential gene expression of infant and pubertal rat Sertoli cells (Sc).Unlike, pubertal Sc, infant Sc are immature and fail to support spermatogenesis. We found exclusive association of 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Microarray is a powerful technique to study differentially expressed genes in large numbers [ 11 ]. Differential gene expression during spermatogenesis has been studied by various researchers using microarray technology studied by us [ 12 , 13 ] and others [ 14 16 ]. These gene expression profiling experiments reveal candidate genes for the regulation of spermatogenesis and fertility as well as targets for innovative contraceptives that act on gene products absent in other somatic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Microarray is a powerful technique to study differentially expressed genes in large numbers [ 11 ]. Differential gene expression during spermatogenesis has been studied by various researchers using microarray technology studied by us [ 12 , 13 ] and others [ 14 16 ]. These gene expression profiling experiments reveal candidate genes for the regulation of spermatogenesis and fertility as well as targets for innovative contraceptives that act on gene products absent in other somatic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we demonstrate a role of homeobox transcription factor MEIS1 in maturation of Sc and, hence, spermatogenesis. We selected Meis1 from the list of transcription factors whose binding sites were found by us to be enriched in the genes which gets up‐regulated in Sc during puberty 16 . As the binding sites of MEIS1 are significantly enriched on the promoter of genes up‐regulated in pubertal Sc, we hypothesized that MEIS1 could be playing an important role in regulating pubertal Sc function which is also associated with robust Gc differentiation, first time after birth.…”
Section: Discussionmentioning
confidence: 99%
“…In a previously reported study from our laboratory, the binding sites of a number of TFs in genes up‐regulated in mature Sc and infant (immature) Sc were identified using TRANSFAC analysis 16 . Analysis of the TRANSFAC data revealed that the binding site for the transcription factor MEIS1 was significantly enriched on the promoters of the genes up‐regulated in functionally mature pubertal Sc.…”
Section: Introductionmentioning
confidence: 98%
“…Another intriguing question that still remains unanswered is how this switch gets established during the juvenile period when the levels of circulating gonadotropins are barely minimal. It is also reasonable to consider that the compromised maturation of Sertoli cells may lead to impaired functioning of these cells with insufficient expression of genes important for regulation of spermatogenesis, as has been shown by us (Das et al, 2013;Mandal et al, 2017). Such a situation may not allow the Sertoli cells to efficiently augment germ cell proliferation and differentiation, even in the phase of elevated hormones, which manifest at puberty.…”
Section: Pubertal Maturation Of Testis Leading To the Spermatogenicmentioning
confidence: 99%
“…This was coupled with high throughput proteomics (like SWATH analysis etc.) to identify factors in infant and pubertal Sertoli cells which are crucial for spermatogenesis (Mandal et al, ). The new information will significantly improve our current understanding of the etiology of some forms of pubertal defects leading to idiopathic male infertility.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%